CRITICAL COMMUNITY PSYCHOLOGY IN EDUCATION: AN ARGUMENT FOR TRANSFORMATIVE AUTONOMY - Nel, Willy (South African Journal of Higher Education, 2016)
Using the concept of transformative autonomy as guide, I speculate about the possibilities of it offering to develop a critical community psychology in education which strengthens education as a public good in our democracy. My speculations are cast against two sets of data; primary school role players’ narratives about the learner support offered and received in their contexts; and high school learners’ understanding of Dewey’s notion of the purpose of progressive education. These data sets were analysed using a qualitative appraisal of the psychopolitical validity of the responses. The parents, teachers and learners of two rural primary schools display psychopolitically valid understandings of learner support as their business first, before it is that of the government. The high school learners (in grade 10 and 11) demonstrated, at least, epistemic psychopolitically valid understandings that progressive education should be for social transformation in a progressive direction. Higher Education, by emphasising transformative autonomy during teacher education, can play a crucial role in framing education as a public good and for the furtherance of democracy. Keywords: Transformative autonomy, critical community psychology, democracy, teacher education, learner support, psychopolitical validity